2012
DOI: 10.1111/j.1600-0501.2012.02497.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular anatomical variations in the anterior palate observed on CBCT images

Abstract: Over 15% of the population studied had additional foramina in the anterior palate, between 1 mm and 1.9 mm wide, with variable locations. In most cases the canals associated with these foramina either presented as a direct extension of the canalis sinuosus, or coursed towards the nasal cavity floor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
152
3
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(195 citation statements)
references
References 19 publications
23
152
3
17
Order By: Relevance
“…The presence of ACs which derived from the CS was not found to be correlated with sex and age groups. Present study revealed similar results and in agreement with other studies available in literature [2,8,16].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The presence of ACs which derived from the CS was not found to be correlated with sex and age groups. Present study revealed similar results and in agreement with other studies available in literature [2,8,16].…”
Section: Discussionsupporting
confidence: 94%
“…Although de Oliveira Santos et al [2] reported that they found 15 females against 13 males with accessory bony canal but they also mentioned that they did not reveal any statistical differences. Although, in this study, it was found a slight tendency to higher prevalence in females similarly as in de Oliveira Santos et al's [2] study, but the results of this article are in agreement with those previous studies in which between-gender differences were not statistically significant (c 2 = 1.099; p = 0.294).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the past, these morphological changes were hardly detected as a result of poor quality images which could lead to intraoperative complications in which the etiology was unknown during a surgical procedure in the anterior maxillary region [4]. The technical developments in diagnostic imaging have increased the accuracy of the diagnostic data obtained, particularly the use of CBCT [5,6]. This article describes an anatomical variation of the CS with the presence of unilateral accessory canals using CBCT images.…”
Section: Introductionmentioning
confidence: 99%